Seasonal PM Management: (II) How Low PM2.5 Concentration in South Korea can be Achieved? 미세먼지 계절관리제: (II) PM2.5 농도 얼마나 낮출 수 있는가? - Bae, Minah; Woo, Jung Hun; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2023)
We quantitatively estimated PM2.5 (Particulate Matter of 2.5 μm or less in diameter) reduction potential of domestic emissions in South Korea during the 2nd Seasonal PM Management (SPM; December 2020 - March 2021). A set of threedimensional air quality model simulations utilizing Community Multi-scale Air Quality (CMAQ) based on the Clean Air Policy Support System 2018 and Satellite Integrated Joint monitoring of Air Quality version 1 emissions inventories (EIs) were applied. Foreign or domestic emissions were reduced by 50% or 100% in turn to estimate the emission impacts in different simulations and/or adjusting approaches. Depending on choice on the perturbation rate and emission source area, EI-based domestic emission impacts ranged from 10.6 to 13.5 μg/m3 (42 - 54%) for the study period. The domestic emission impact estimated from a 100% reduction of national emissions was 2.9 μg/m3 higher than that from a 50% reduction. It implies that appreciable nonlinear relationship exists between domestic emissions and the PM2.5 concentrations. Meanwhile, the EI-based PM2.5 simulations were underestimated by 7% in China and overestimated by 4% in South Korea, respectively. Considering the simulation uncertainty, domestic and foreign impacts were adjusted based on the PM2.5 observations. After the adjustment, the domestic impacts were assessed to 8.6 - 13.0 μg/m3 that can be interpreted as the maximum domestic PM2.5 reduction potential. When a 100% reduction of domestic emissions was assumed, the national PM2.5 concentration during the SPM barely satisfied the annual average air quality standard level (15 μg/m3). On the other hand, it was predicted that simultaneously reductions of domestic and foreign emissions by 50% lowered the PM2.5 concentration in South Korea during the SPM to 13.0 μg/m3. Considering that it is realistically impossible to reduce total domestic emissions (i.e., 100%), international cooperation among neighboring countries is imperative to achieve the target PM2.5 concentration in South Korea
Keywords: Emission reduction potential; Local emission impact; Long-range transport; PM2.5; Seasonal PM Management